Hydroxypropyl chitosan nail lacquer of ciclopirox-PLGA nanocapsules for augmented in vitro nail plate absorption and onychomycosis treatment - Eman Yahya Gaballah; Thanaa Mohammed Borg; Elham Abdelmonem Mohamed (Taylor & Francis Group, 2022)
Onychomycosis accounts for 90% of nail infections worldwide. Topical therapy provides localized effects with minimal adverse systemic actions, yet its effectiveness is limited by minimal drug permeation through the keratinized nail plate. Ciclopirox (CIX) is a FDA-approved broad-spectrum antimycotic agent. However, the complete cure with its nail lacquer (8% w/v) may continue for one year with a high cost. Therefore, poly lactide-co-glycolide (PLGA) nanocapsules (NCs) of CIX were prepared by nanoprecipitation and optimized through a 23 factorial design to be incorporated into hydroxypropyl chitosan (HPCH) based nail lacquer. Nail hydration, in vitro nail absorption, minimum inhibitory concentration (MIC), inhibition zones and ex vivo fungal growth on nail fragments were evaluated. The optimized NCs of CIX based on 100 mg PLGA 2 A and lipoid S75 showed a mean diameter of 174.77 ± 7.90 nm, entrapment efficiency (EE%) of 90.57 ± 0.98%, zeta potential (ZP) of −52.27 ± 0.40 mV and a prolonged drug release. Nail lacquer of the optimized NCs exhibited a higher stability than NCs dispersion. Compared to CIX solution (1% w/v), the respective decrease in MIC for NCs and their lacquer was four- and eight-fold. The lacquer superiority was confirmed by the enhancement in the nail hydration and absorption by 4 and 2.60 times, respectively, relative to CIX solution and the minimal ex vivo fungal growth. Therefore, HPCH nail lacquer of (1% w/v) CIX-PLGA-NCs can be represented as a potential topical delivery system for enhanced in vitro nail absorption and therapeutic efficacy against onychomycosis at a low dose.